Using PELA to Predict International Business Students’ English Writing Performance with Contextualised English Writing Workshops as Intervention Program - Wong, Caroline; Delante, Nimrod; Wang, Pengji (Journal of University Teaching and Learning Practice, 2017)
This study examines the effectiveness of Post-Entry English Language Assessment (PELA) as a predictor of international business students’ English writing performance and academic performance. An intervention involving the implementation of contextualised English writing workshops was embedded in a specific business subject targeted at students who performed poorly on the PELA. The results reveal that PELA is a better predictor of students’ English writing performance and academic performance than their own perceptions of their English language skills, and the contextualised English writing workshops proved to be a worthwhile intervention. Students with low scores on the PELA showed significant improvement in their overall academic performance in the subject after the intervention. This improvement was reflected in their score on a major written assignment (English writing performance) and their final grade for the subject (academic performance). Moreover, students’ perceptions captured through a focus group interview and an online survey indicated a positive correlation between the intervention program and learning outcomes. The implications of this study underscore the need for regular university wide implementation of a PELA to determine students’ English writing proficiency and to align English writing workshops with tutorial and assessment activities as a pedagogic response to PELA outcomes. This approach will help students improve not only their English writing skills but also their overall academic performance.